Treatment Patterns of Tocilizumab Utilization for Progressive Respiratory Distress during the COVID-19 Pandemic - Barber, Kimberly R.; Hartnett, Kristen; Hella, Jennifer R.; Caloia, Roya Z.; LaBond, Virginia (International Journal of Statistics in Medical Research, 2022)
Purpose: This study’s objective was to describe treatment patterns of patients receiving then experimental drug tocilizumab for severe respiratory illness. Methodology: It is a retrospective case series of patients receiving tocilizumab for COVID-19 at a 380-bed hospital between 03/01/202 and 05/31/2020. Treatment patterns for tocilizumab for this series of ICU patients was modeled using a Spearman rho correlation for ranked associations. Results: There was significant variation in frequency and serial testing of inflammatory markers. There was no correlation between tocilizumab initiation and worsening respiratory status (r=0.19, p=.48) or between days since dosing and survival (R= -0.02, p= .95). No clear pattern emerged from tocilizumab administration during the pandemic. Conclusion: Protocols for untested new treatments are needed to overcome the uncertainty physicians face during pandemics.